Problem of Periodization of the World History in Soviet Social Science of the 1920s - E. P. Emelyanov (Научный диалог)
The article is devoted to the development of the periodization of world history in Soviet social science of the 1920s. Various options for periodization that existed in the educational literature on this discipline in the specified period are considered. It is noted that Soviet social scientists abandoned the traditional division of history into Antiquity, the Middle Ages and the New Time and introduced a new approach to the periodization of world history: primitive (including one or two formations in different versions), feudalism, commercial capitalism and industrial capitalism. The methodological basis of this approach associated with the works of K. Marx, E. Meyer and M.N. Pokrovsky is revealed. A hypothesis is proposed according to which such an approach to world history meant the recognition by the Soviet social scientists of the non-linear nature of the historical process and the endowment of historical time with meaningful, class, characteristics. The author of the article believes that these processes in Soviet social science corresponded to a “temporal turn” in European thought of the first third of the twentieth century, characterized by the consideration of time as a process that has semantic content and depends on the subject. It is noted that, despite the return of the terms Antiquity, Middle Ages, and New Time in the 1930s, this periodization already included an idea of the class nature of historical time, which remained in Soviet science until the end of the existence of the USSR.